Exploring Financial Performance and Audit Opinions in Indonesian Central Government Agencies - Zakaria, Adam (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research aims to develop an accurate prediction model for determining the audit opinions issued by the State Audit Agency based on various factors, such as leverage ratios, solvency ratios, liquidity ratios, revenue effectiveness ratios, expenditure efficiency ratios, and surplus. Observations were conducted on 254 audit financial reports from the period 2017 to 2019 from 86 central government agencies. The resulting prediction model complies with the specified model requirements. Out of the six independent variables tested, only two were found to have a statistically significant impact on their audit opinions, namely liquidity ratios and revenue effectiveness ratios. Meanwhile, the other four variables, including leverage ratios, solvency ratios, expenditure efficiency ratios, and surplus, did not have a statistically significant effect. The results of this study provide insights to ministries and government agencies regarding the importance of financial performance in predicting audit opinions.Keywords: Bureaucratic Reform; Public Sector Audit; Financial Performances; State Revenue; Fund Management Abstrak Penelitian ini bertujuan untuk mengembangkan model prediksi yang tepat untuk menentukan opini audit Badan Pemeriksa Keuangan berdasarkan berbagai faktor, seperti rasio leverage, rasio solvabilitas, rasio likuiditas, rasio efektivitas pendapatan, rasio efisiensi pengeluaran, dan surplus. Pengamatan dilakukan pada 254 laporan keuangan audit dari periode 2017–2019 yang berasal dari 86 instansi pemerintah pusat. Model prediksi yang dihasilkan mematuhi persyaratan yang ditetapkan. Dari enam variabel independen yang diuji, hanya dua yang terbukti memiliki pengaruh signifikan terhadap opini audit, yaitu rasio likuiditas dan rasio efektivitas pendapatan. Sementara empat variabel lainnya, yaitu rasio leverage, rasio solvabilitas, rasio efisiensi pengeluaran, dan surplus, tidak memiliki pengaruh yang signifikan secara statistik. Hasil studi ini memberikan wawasan kepada kementerian dan lembaga pemerintah tentang pentingnya kinerja keuangan dalam memprediksi opini audit. Kata Kunci: Reformasi Birokrasi; Audit Sektor Publik; Kinerja Keuangan; Pendapatan Negara; Manajemen Dana